Republic of Estonia : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This Selected Issues paper of the Republic of Estonia reviews the current account deficits, sustainability, and external solvency in the Baltic countries. The paper describes labor market trends in Estonia after the transition, institutional makeup of the market, and its effects on unemployment. The paper also discusses developments in regional unemployment, effects of regional disparities on average unemployment, and policy recommendations. Finally, the statistical appendix highlights the IMF's projections and estimates for the Republic of Estonia.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet